2018
DOI: 10.3390/app8112108
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Properties of Enterobacter sp. LX3 Capable of Producing Indoleacetic Acid

Abstract: Indoleacetic acid (IAA) can act as a phytohormone to modulate plant growth and development, thus persistent search for IAA-producing microbes is underway for a potential application in promoting plant growth. In this paper, an IAA-producing bacterium was obtained from maize rhizosphere in biochar-amending field. This strain is a Gram-negative and facultative anaerobic rod. Phenotypic examination and 16S rRNA gene sequencing suggest that this strain is a new strain of the Enterobacter species. We designated thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In this work, both strains of E. casseliflavus showed no gelatin hydrolysis. Similarly, the results of no gelatin hydrolysis of Enterobacter spp., P. pentosaceus, certain A. pasteurianus, M. guilliermondii TC15, and S. cerevisiae TC6 in this work were in accordance with the previous reports showing the same species with no gelatinase activity (Fakruddin et al 2017;Chi et al 2018;Zajc et al 2019). This indicated greater potential use as probiotics since these strains are unlikely to express gelatinase, a metalloendopeptidase, which is able to degrade hemoglobin, insulin, collagen, casein, fibrinogen and gelatin (Kanemitsu et al 2001) and thus may harm the hosts.…”
Section: Discussionsupporting
confidence: 92%
“…In this work, both strains of E. casseliflavus showed no gelatin hydrolysis. Similarly, the results of no gelatin hydrolysis of Enterobacter spp., P. pentosaceus, certain A. pasteurianus, M. guilliermondii TC15, and S. cerevisiae TC6 in this work were in accordance with the previous reports showing the same species with no gelatinase activity (Fakruddin et al 2017;Chi et al 2018;Zajc et al 2019). This indicated greater potential use as probiotics since these strains are unlikely to express gelatinase, a metalloendopeptidase, which is able to degrade hemoglobin, insulin, collagen, casein, fibrinogen and gelatin (Kanemitsu et al 2001) and thus may harm the hosts.…”
Section: Discussionsupporting
confidence: 92%
“…Using the same concentration of tryptophan as the precursor (1 mL/20 mL broth), Ng et al [45] found that Enterobacter gergoviae and Bacillus amyloliquefaciens produced IAA in the of range of 3.56-24 µg mL −1 . IAA act as a phytohormone to regulate plant growth and development, which leads to a persistent search for IAA-producing microbes for a potential application in promoting plant growth [46]. Enterobacter sp.…”
Section: Effect Of Fermentation On the Indole Acetic Acid Productionmentioning
confidence: 99%
“…Enterobacter sp. was found to have produced up to 200 mg L −1 of IAA using 1-tryptophan in NB medium [46]. The IAA production is vital in plant root elongation and root hair development [13].…”
Section: Effect Of Fermentation On the Indole Acetic Acid Productionmentioning
confidence: 99%
“…Genes scrA and scrB genes in Klebsiella pneumoniae, play a role in sucrose hydrolysis (Titgemeyer et al 1996). The genus Enterobacter is a bacterium that is often found in the rhizosphere of plants, and most of them were reported to degrade sucrose (Khalifa et al 2016;Chi et al 2018). According to Wu and Birch (2005), Pantoea dispersa, as a part of ordo Enterobacterales, also produces highly efficient sucrose isomerase that can carry out two catalytic processes, hydrolysis, and isomerization of sucrose, with the final results of glucose and fructose in a ratio of 1: 1.…”
Section: Discussionmentioning
confidence: 99%